Democracy as a reflection of human nature : deconstructing the myths (2014)
Humanity has proven to be both puzzling and ambiguous by way of its instinctive pursuit of happiness through reason. Tending to act rationally, while fluctuating between stoic and epicurean inclinations, preferences, beliefs and interpretations often serve to fulfill a presumably ultimate goal: to avoid pain and to seek pleasure. Thus, when human nature is reduced to its core elements, a striking fact is made manifest: though every person has individual and subjective pursuits, and seeks to maximize private utility by way of knowledge and power, humans need to create associations to satisfy their everyday needs. As Aristotle (trans. 2013) argued, “man is by nature a political animal” (bk I, sect. II); then, community is the essential foundation to preserve and achieve human flourishing. Hence, Western modernity requires a perception and understanding that takes into account the idea of interdependence between people. While such a society is the result of human interaction, which represents a tool for human beings to fulfill their ultimate private preferences, a multiplicity of interests can offset one another. It is, therefore, necessary for individual members to coordinate their actions within their given group in order to secure an average shared benefit. However, if coordination is not possible, then there will be no shared benefit. Furthermore, within human nature, there is another struggle that creates a conflict of interest where the needs of a community, whose fundamental components include reciprocity, clashes with the needs of the individual. At first sight, two possible methods emerge to overcome this dissension: 1) to value community over subjective preferences, exercising honesty and empathy; or 2) to act strategically, beyond moral values, anticipating actions that hinder the reduction of subjective interests in order to maximize utility.